2011
DOI: 10.1007/s12663-011-0250-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Intravenous Tramadol Versus Diclofenac for Preventing Postoperative Pain After Third Molar Surgery: A Comparative Study

Abstract: Purpose The purpose of this study was to compare the analgesic efficacy of a single-dose of preoperative intravenous tramadol versus diclofenac in preventing pain after third molar surgery. Materials and Methods Fifty patients undergoing elective third molar surgery were randomly assigned into one of the two groups (25 in each group): Group 1 received diclofenac 75 mg, and Group 2 received tramadol 50 mg intravenously preoperatively before the surgery. After injection of the study drugs, the impacted third mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Preferential cyclo oxygenase -2 inhibitors Diclofenac [15,17,18,27,36,37], Meloxicam [42], Nimesulide [40]. 7.…”
mentioning
confidence: 99%
“…Preferential cyclo oxygenase -2 inhibitors Diclofenac [15,17,18,27,36,37], Meloxicam [42], Nimesulide [40]. 7.…”
mentioning
confidence: 99%
“…Preemptive analgesia may decrease post-operative pain in the clinic. In previous clinical studies, preemptive administration of an analgesic agent has been shown to improve postoperative pain control in case of laparoscopic radical prostatectomy [ 28 ], thoracotomy [ 29 ], and third molar extraction [ 30 31 ]. Additionally, preemptive application of 1% lidocaine for 10 minutes prior to L4 and L5 bilateral dorsal rhizotomy significantly attenuates hindlimb mechanical allodynia in patients with failed back surgery syndrome [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oncul et al compared preoperative IV diclofenac sodium with IV paracetamol (acetaminophen) and Lornoxicam and concluded that although all were equally effective on postoperative pain ( 16 ). Diclofenac was reported to be better in controlling postoperative pain compared to tramadol and ketorolac but less compared to piroxicam and nimesulid and tenoxicam ( 17 - 21 ).…”
Section: Discussionmentioning
confidence: 99%